A145 BREASTFEEDING INCREASES COLONIC INFLAMMATION IN INFANTS BORN FROM HEALTHY MOMS, WHICH EFFECT IS LACKING IN INFANTS BORN FROM MOMS WITH IBD. (1st March 2018) - Nguyen, V V; Ambrosio, L; Dunsmore, G; Agrawal, A; Hotte, N; Dieleman, L A; Halloran, B P; Kroeker, K I; Fedorak, R; elahi, S; Madsen, K; Huang, V
Abstract: Background: Breastfeeding (BF) is recommended for at least 6 months postpartum because of the beneficial components of breast milk. Studies show that there is a healthy inflammatory response (measured by fecal calprotectin (FCP)) in healthy full term breastfed infants. Whether this effect of breastfeeding on infant intestinal inflammation is affected by maternal IBD and IBD therapies is unknown. Aims: In this study, we compared the FCP levels in infants born to and breastfed by healthy mothers with those born to and breastfed by IBD mothers. Methods: Mothers with IBD (CD or UC) and healthy mothers (HC) were consented to collect their infant's stool at delivery, post-partum 3 months, and 6 months. FCP was extracted and measured by ELISA. Breastfeeding status was documented as exclusively (EBF) or not exclusively breastfed (non-EBF). IBD medications (no medications, 5-ASA only, thiopurine, biologics) was documented. Results: There were 21 (5 CD, 12 UC, 4 HC) PP3 months stools and 22 (5 CD, 10 UC, 6 HC) PP 6 months stools. Only 11 infants (4 CD, 4 UC, 3 HC) were exclusively breastfed until 6 months. As shown in Figure 1, at 3 months post-partum breastfed non-IBD infants have higher FCP than non-EBF infants or infants from IBD moms, the latter category irrespectively of BF or not. This effect of breastfeeding on infant FCP seems to disappear at 6 months post-partum. At PP 3, this lack of increased FCP in breastfed infants from IBD moms was not affected by oral 5-ASA or biologics, although the numbers are too small to draw definitive conclusions. Conclusions: Infant intestinal inflammation is increased by breastfeeding among healthy infants, but not in IBD infants. Further investigation into the infant's intestinal inflammation by maternal clinical disease activity, and IBD medications through breast milk are currently in progress. Funding Agencies: CEGIIR University of Alberta